THE EFFECT OF SOCIAL MEDIA ON SYNONYMS IN EVERYDAY LANGUAGE FROM A SEMANTIC PERSPECTIVE - Esra Delima Hutabarat; Bernieke Anggita Ristia Damanik (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to examine how social media affects semantic changes in the use of everyday language, particularly in synonym usage. The objective is to explore the impact of social media on the semantic shift and variation of synonyms in daily communication. A descriptive qualitative approach was employed in this research. The data were collected through observation of language use on social media platforms such as Twitter and TikTok, supported by documentation and analysis of user-generated content that showcases frequent synonym usage. The findings reveal that social media significantly influences the choice and meaning of synonyms in everyday language, often encouraging more expressive, creative, and informal word usage. Additionally, the study highlights several forms of semantic shifts, such as broadening, narrowing, and meaning change, which are driven by social and cultural interactions in the digital space. These results demonstrate that social media plays a crucial role in shaping contemporary language dynamics from a semantic perspective.